AN ERROR ANALYSIS ON ACTIVE AND PASSIVE VOICE ON STUDENTS’ WRITING (Lexeme : Journal of Linguistics and Applied Linguistics, 2019)
AbstractThis study is aimed to find out and describe the students' error on active and passive voices on students’ writing skill especially in local errors, inter-lingual errors and intra-lingual errors. Everybody who considers English has precisely made a few blunders, particularly the students in Junior secondary school or in Senior High School.. Active contrasts with passive mainly. For most active clauses, there is a corresponding passive clause, which has almost exactly the same meaning, but a different emphasis. The research was done at public senior high school in CISEENG, BOGOR, and it was done on March 2018. The researcher did the research in the science class on 12th grade. The method, which was used in this research, is the qualitative method. In this case the researcher asked the English teacher on that school to get the students’ writing result. The data used in this research is the error on active and passive voices on students’ writing at public senior high school. To get the data, the students wrote their own text. The result shows that active voice errors are more than passive voice errors. It means that the students still have difficulties to make the correct English structure in active voice.Keywords: Error Analysis, Aactive-Passive Voice, Students’ Writing.